Principal’s Leadership During the Covid-19 Pandemic for Face-to-Face Learning - Novarini, Rita (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2023)
The goal of this paper is to outline the leadership strategies used by school administrators during the first year of restricted face-to-face instruction following the Covid-19 pandemic. Using face-to-face instruction in accordance with the Joint Decree (SKB) of 4 Ministers, Number 737 of 2020, during the COVID-19 pandemic. Descriptive qualitative research is what this study is. employing observation, interviews, and literature studies as data collection methods. According to the study's findings, Kayuagung 4 Public Middle School needs to make preparations before implementing limited face-to-face instruction. These preparations include having health protocol facilities and getting letters from parents approving the program. After limited face-to-face learning and online learning, this research offers a novel understanding of face-to-face learning in junior high schools.